Screen Time and Emotional Development Among Indonesian Preschoolers: A Comparative Study Across Socioeconomic Contexts in Jakarta - Widia Sari; Adam Astrada; Visya Septiana; Rian Adi Pamungkas (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: The widespread use of screen media among preschool-aged children has raised concerns about its impact on emotional development, particularly within socioeconomically diverse populations. Although excessive screen time has been associated with emotional difficulties in early childhood, few studies have explored how socioeconomic status (SES) moderates these effects, especially in Indonesia. This understanding is critical for healthcare professionals, including nurses, involved in child health promotion and family-centered care. Methods: This comparative cross sectional study employed a quantitative approach and was conducted in two kindergartens in West Jakarta, Indonesia, from November to December 2024. A total of 80 preschool aged children were enrolled, with 40 preschooler from a high SES and 40 from a low SES. Data were collected through structured parent questionnaires that captured screen time characteristics (duration, frequency, content type, and parental supervision). Ethical approval was obtained from the Health Research Ethics Committee of Universitas Esa Unggul (Approval Number: 0925-01.135/DPKE-KEP/FINAL-EA/UEU/II/2025). And all participants parent provided written informed consent prior to participation. Results: The primary outcome of the study was the association between screen time characteristics and emotional development in preschool-aged children. The study revealed that increased screen time duration and frequency were significantly associated with heightened emotional development concerns, particularly among children from lower socioeconomic backgrounds. Parental supervision during screen use appeared to serve as a protective factor, especially in the high SES group, where exposure to educational content was also linked to more positive emotional outcomes. Statistical analysis demonstrated strong positive correlations between screen time and emotional difficulties across both groups (p<0.001), with stronger correlation coefficients in the low SES group. Although the chi- square test indicated a tendency for educational content to be associated with better emotional outcomes in high SES children (p=0.060), the result was not statistically significant. Notably, the protective effect of educational content was limited among the low SES group, suggesting that contextual factors and access to supportive resources may influence the effectiveness of screen based learning. Conclusion: These findings underscore the need for healthcare-Led interventions to promote effective digital parenting, particularly among socioeconomically disadvantaged families. Family-centered health education programs focusing on screen time management are essential for nurses and other healthcare professionals to mitigate emotional development risks and support equitable health outcomes in the digital era.